Определение электрофизических параметров полупроводящих экранов високовольтных силовых кабелей с полимерной изоляцией - Мотко, Р. П.; Пономарева, А. П.; Сокол, С. А. (НТУ "ХПИ", 2016)
Рассмотрена информация о методах оценки электрофизических параметров полупроводящих экранов высоковольтных силовых кабелей с полимерной изоляцией. Определение характеристик полупроводящих экранов – актуальная задача в практике испытаний кабелей с высоковольтной изоляцией. Выполнен анализ влияния частоты на точность измерения электропроводимости и диэлектрической проницаемости полупроводящих материалов. Проанализировано влияние частичных разрядов на изоляцию из сшитого полиэтилена. Указаны причины возникновения частичных разрядов, а также методы по уменьшению амплитуды и полного устранения их. Исследован способ измерения частичных разрядов. Сопоставлены данные разных источников.

Reviewed information on methods to estimate physical properties of the semiconducting screens high voltage power cables with polymeric insulation. Characterization of semiconducting screens – an urgent task in the practice tests of high voltage cables with insulation. The analysis of the influence of frequency on the accuracy of the measurement of conductivity and dielectric constant of semiconducting materials has executed. Analyzed the influence of partial discharges on the XLPE insulation. States the reasons for the occurrence of partial discharges, as well as methods for reducing the amplitude and eliminate them. Researched method of measuring partial discharges. Mapped data from different sources. The problem of determining the characteristics of the semiconducting screens need to be addressed depending on specific situations. In the case of the high-frequency range (for example: lightning impulse, the analysis of partial discharges) can be based on the data of the above method.
Determination of physical parameters of the semiconducting screens high voltage power cables with polymeric insulation
Keywords: кабели питания; преимущества изоляции; сшитый полиэтилен; полупроводящие материалы; частичные разряды; high voltage power cable; semiconducting screen; partial discharge; polymer insulation; cross-linked polyethylene